WY PENGELOLAAN SAMPAH DAN PENINGKATAN KESADARAN LINGKUNGAN MELALUI KULIAH KERJA NYATA MANDIRI DI DESA MEDAN KRIO - Willy Yusnandar (GERAKAN EDUKASI DAN MASYARAKAT NUSANTARA, 2026)
Medan Krio Village is an area with a fairly high population density in Sunggal District, Deli Serdang Regency. The main problem faced by the community service partners in this village is the low public awareness in waste management, marked by the habit of littering which clogs drainage channels, causes water pooling, and reduces environmental comfort. This community service aims to solve these problems through an Independent Community Service Program (KKN Mandiri) focusing on waste management and increasing environmental awareness. The methods applied include field observation, in-depth interviews, educational socialization, joint community action, as well as the implementation of digital technology to support local MSMEs. The results of the implementation of community service show a significant increase in residents' awareness, the availability of facilities for sorting organic and non-organic waste in public spaces, as well as the growth of creativity among elementary school students in recycling used goods (plastic bottles) into economical piggy banks with educational financial value. In addition, aspects of strengthening the local economy were achieved through the digitalization of MSME marketing locations using Google Maps to expand market reach. The success of this program was fully supported by the active participation of village officials and the enthusiasm of the local community, although the challenge of limited time requires the program to continue independently by the local community. Keywords: Waste Management; Environmental Awareness, Recycling, MSME.